PERAN ORGANISASI SEKAA TERUNA TERUNI DALAM PEMBENTUKAN KARAKTER KEPEMIMPINAN PADA GENERASI MUDA DI DESA DARMASABA - linda sari, ni wayan; SUKA ARJAWA, I GUSTI PUTU BAGUS; KRISNA ADITYA, I GUSTI NGURAH AGUNG (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
ABSTRACT PERAN ORGANISASI SEKAA TERUNA TERUNI DALAM PEMBENTUKAN KARAKTER KEPEMIMPINAN PADA GENERASI MUDA DI DESA DARMASABA This research analyzes and explains the role of the Sekaa Teruna Teruni organization in forming leadership character in the younger generation in Darmasaba Village. The approach used in this research is qualitative with a descriptive type and analysis using George Herbert Mead's socialization theory. Organizations, both formal and informal, play an important role in shaping individual identity and character. Organizations not only provide structures and frameworks for social interaction, but also become a forum for the development of values, norms and skills that are essential in social life (Sutedjo & Mangkunegara, 2013). Organizational life for teenagers in self-development, especially fostering leadership character, one of which is through Sekaa Teruna Teruni. Based on the research that has been carried out, it is known that the Sekaa Teruna Teruni organization in Darmasaba Village plays a good role in developing leadership character, such as training everyone to be able to speak in public, dare to accept different opinions, manage many people, apart from that, the problem solving process is carried out by means of discussion. Sekaa Teruna Teruni is also an initiator of positive activities in the surrounding environment. However, in practice there are several obstacles such as delays in activity times, challenges in maintaining motivation, awareness and involvement of members, as well as funds and facilities in carrying out youth activities. Keywords: Sekaa Teruna Teruni, Leadership Character, Young Generation in Darmasaba Village.